Methodological Background of the Amersham Amerlex Free Thyroxine RIA - Midgley, J. E. M. (Nuklearmedizin - NuclearMedicine, 1982)
This contribution describes the essential rules underlying a valid estimation of FT4 and compares the way in which various methods deviate from ideal behaviour. The Amerlex(R) FT4 RIA test has been validated by several approaches. A practical demonstration of the ability of various methods to correct for differences in T4-binding protein concentration has been made by independent studies in a UK hospital on euthyroid non-pregnant, euthyroid contraceptive and euthyroid pregnant women. The Amersham kit has been shown to correspond closely to theoretical expectations for FT4 values in these groups.